Is sexual risk taking behaviour changing in rural south-west Uganda? Behaviour trends in a rural population cohort 1993–2006. (23rd March 2009) - Biraro, S; Shafer, L A; Kleinschmidt, I; Wolff, B; Karabalinde, A; Nalwoga, A; Musinguzi, J; Kirungi, W; Opio, A; Whitworth, J; Grosskurth, H
Abstract : Objective: To describe sexual behaviour trends in a rural Ugandan cohort in the context of an evolving HIV epidemic, 1993–2006. Methods: Sexual behaviour data were collected annually from a population cohort in which HIV serological surveys were also conducted. Behaviour trends were determined using survival analysis and logistic regression. Trends are reported based on the years in which the respective indicators were collected. Results: Between 1993 and 2006, median age at first sex increased from 16.7 years to 18.2 years among 17–20-year-old girls and from 18.5 years to 19.9 years among boys. Both sexes reported a dip in age at sexual debut between 1998 and 2001. One or more casual partners in the past 12 months among men rose from 11.6% in 1997 to 12.7% in 2004 and then declined to 10.2% in 2006. Among women it increased from 1.4% in 1997 to 3.7% in 2004 and then reduced to 1.4% in 2006. The rise in casual partners between 1997 and 2004 was driven mainly by older age groups. Trends in condom use with casual partners varied by age, increasing among those aged 35+ years, declining in the middle age groups and presenting a dip and then a rise in the youngest aged group (13–19 years). Conclusion: Among youth, risky behaviour declined but increased in the late 1990s/early 2000s. Among those aged 35+ years, condom use rose but casual partners also rose. Several indicators portrayed a temporary increase in risk taking behaviour from 1998 to 2002.